MUTU MADARASAH DAN PROFESIONALISME GURU: TUNTUTAN DI ERA GLOBALISASI - Yuniar Yuniar (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2013)
The quality of madrasah and professionalism of teachers are an important element that continues under the spotlight of various circles. It is considered reasonable for the development of madrasas in quantity does not accompanied by an increase in the quality / grade. In this era of globalization, in order to remain in existence, the school must pay attention to the quality. To that end, realize the quality of madrasah, as the essential prerequisite is the professionalism of teachers. Teachers are professionals who have the four competencies that pedagogic competence, personal, professional and social. Teachers are professional and qualified madrassas demands that must be realized in the era of globalization. This is reinforced by the emergence of the Law No. 14 Year 2005 on Teachers and Lecturers. The existence of this law meant that teachers have sufficient competence to the intellectual life of the nation.